Effect of etching time on optical and morphological features of N-type porous silicon prepared by photo-electrochemical method - Thahe, Asad A. (Penerbit UTM Press, 2016)
Achieving efficient visible photoluminescence from porous-silicon (PSi) is demanding for optoelectronic and solar cells applications. Improving the absorption and emission features of PSi is challenging. Photo-electro-chemical etching assisted formation of PSi layers on n-type (111) silicon (Si) wafers is reported. Samples are prepared at constant current density (~30 mA/cm2) under varying etching times of 10, 15, 20, 25, and 30 min. The influence of etching time duration on the growth morphology and spectral properties are inspected. Room temperature photoluminescence (PL) measurement is performed to determine the optical properties of as-synthesized samples. Sample morphologies are imaged via Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The thickness and porosity of the prepared samples are estimated using the gravimetric method. The emission and absorption data is further used to determine the samples band gap and electronic structure properties. Results and analyzed, interpreted with different mechanisms and compared.